2019
DOI: 10.3341/kjo.2018.0106
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Dexamethasone Implantation in Intravitreal Bevacizumab Treatment-resistant Pseudophakic Cystoid Macular Edema

Abstract: Purpose To evaluate the changes in visual acuity (VA) and central macular thickness (CMT) after intravitreal dexamethasone (IVD) implantation in intravitreal bevacizumab (IVB) treatment-resistant cases with pseudophakic cystoid macular edema (PCME). Methods This study included 10 PCME cases who underwent uneventful phacoemulsification and intraocular lens implantation with similar methods and six PCME cases referred to our hospital for treatment of low VA after cataract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Before the dexamethasone implant was introduced, triamcinolone acetonide was tested in a few larger and smaller studies, proving its efficacy in improving macular morphology and function in IGS [33,35,[65][66][67]. Later studies show significant improvements after IVD administration without serious side effects [27,[29][30][31][32]34]. The most recent large retrospective study from 2020 highlighted the benefits of early intervention and reported significantly larger visual gains when IVD was administered within 4 weeks of diagnosis [27].…”
Section: Discussionmentioning
confidence: 99%
“…Before the dexamethasone implant was introduced, triamcinolone acetonide was tested in a few larger and smaller studies, proving its efficacy in improving macular morphology and function in IGS [33,35,[65][66][67]. Later studies show significant improvements after IVD administration without serious side effects [27,[29][30][31][32]34]. The most recent large retrospective study from 2020 highlighted the benefits of early intervention and reported significantly larger visual gains when IVD was administered within 4 weeks of diagnosis [27].…”
Section: Discussionmentioning
confidence: 99%
“…They are considered primary treatment in many instances. Steroid are administered topically, systemically, intravitreally 15 . They can also be given in posterior subtenon space.…”
Section: Discussionmentioning
confidence: 99%
“…Barone et al identified a positive effect with intravitreal bevacizumab [14], while Splitzer et al illustrated the effect to be nonexistent [15]. In studies of bevacizumab-resistant cases, the use of a dexamethasone intravitreal implant improved corrected distance visual acuity (CDVA) and reduced central foveal thickness (CFT) [16,17]. Triamcinolone acetonide (TA) was shown to mediate similar effects compared to the dexamethasone implant [18][19][20], while other studies have recognized the need for more frequent injections due to the more temporary effect than with the dexamethasone implant [21,22].…”
Section: Introductionmentioning
confidence: 99%